Differential tissue expression of erythroblast macrophage protein in a MRL/lpr mouse model of lupus. (June 2019) - Fan, H; Li, N; Fan, P; Hu, X; Liang, K; Zhang, S; Cheng, X; Wu, Y
Objective: The objective of this study was to observe the expression features of erythroblast macrophage protein (EMP) between the tissues of MRL/lpr mice, a mouse model of systemic lupus erythematosus (SLE), and control mice. Methods: We examined the serum ANA in both mice groups through indirect immunofluorescence (IIF). Expression features of EMP in bone marrow, liver, renal, spleen, brain, and lung tissues of the MRL/lpr mice and control mice groups were followed using quantitative real-time polymerase chain reaction (Q-PCR). Meanwhile, the expression of EMP was located through immunohistochemical (IHC) studies and the expressive cell identified through double immunofluorescent labeling. Results: IIF showed that lupus mice have strong positive fluorescence, but no significant fluorescence was observed in control mice. Q-PCR detection revealed that EMP was expressed in the marrow, liver, renal, spleen, lung, and brain tissues of lupus mice. The highest levels were observed in the bone marrow, but there was no statistical difference between these tissues. EMP mRNA expression in the liver ( t  = 2.747, p  = 0.01) and bone marrow ( t  = 3.853, p  = 0.008) of lupus mice was significantly higher than in the control mice. However, no differences in EMP mRNA expression were observed in the renal, spleen, lung, and brain tissues between the lupus and control mice ( p  > 0.05). In addition, the IHC results showed that EMP protein is ubiquitously expressed in all of the tissues of the lupus and control mice. The positive expression rate in the bone marrow and liver tissues of the lupus mice was higher than in the control mice, but without an obvious difference in the other tissues. The double IF staining method shows that EMP protein was expressed in macrophages in the tissues of the lupus mice and the control mice. Conclusions: Our data showed that EMP is ubiquitously expressed in macrophages at all of the tissues of the lupus and control mice. However, the expression of EMP in bone marrow and liver tissues of lupus mice was higher than in the control mice, which indicates that EMP may be important in the development of SLE.